Operation Iraqi Freedom - Kusnetz, Marc.; NBC News. (Kansas City, MO : Andrews McMeel Pub., 2003)
This book and DVD package written and produced by NBC News presents a chronological narrative of reporting from the field supplemented by interviews and anchored broadcasts from Qatar, Kuwait, and the United States.
"22 historic days in words and pictures"--Jacket.
"Foreword and DVD narration by Tom Brokaw"--Jacket.
"A full-length DVD produced by NBC News expressly for this volume presents the highlights of the network's war coverage"--Jacket.
Keywords: 2003-2011; Iraq War, 2003-2011 -- Television and the war; Electronic news gathering -- United States; Television broadcasting of news -- United States; z; z; Electronic news gathering; Television broadcasting of news; War and television; Iraq; United States